2012
DOI: 10.1080/00377996.2011.596859
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Social Issues Related to Teaching about the Federal Budget, Federal Debt, and Budget Deficit in Fifty State High School Social Studies Standards

Abstract: This study of all fifty state, high school social studies curriculum standards found a lack of attention in the vast majority of state standards to the federal budget, federal debt, and budget deficit, topics of significant concern. These concepts are important to teaching about economics in the United States since they lie at the center of contemporary debates about the health of the nation's economy and its long-term viability. Our research discovered broad variation among states in the degree of specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…For example, Troia and Olinghouse (2013) analyzed the extent to which the CCSS ELA standards addressed 36 evidence-based practices of writing assessment and instruction. Marri, Crocco, Shuttleworth, Gaudelli, and Grolnick (2012) analyzed state social studies standards to determine the amount and types of attention devoted to economics education. Across these examples, researchers argue for a focus on the content of standards documents because expectations for student learning likely influence the instruction students receive.…”
Section: Focus On Standards Documentsmentioning
confidence: 99%
“…For example, Troia and Olinghouse (2013) analyzed the extent to which the CCSS ELA standards addressed 36 evidence-based practices of writing assessment and instruction. Marri, Crocco, Shuttleworth, Gaudelli, and Grolnick (2012) analyzed state social studies standards to determine the amount and types of attention devoted to economics education. Across these examples, researchers argue for a focus on the content of standards documents because expectations for student learning likely influence the instruction students receive.…”
Section: Focus On Standards Documentsmentioning
confidence: 99%
“…One study examined state standards, one study critiqued neoclassical curricula but was written before the publication of the 1997 version of the Voluntary National Content Standards in Economics ( Voluntary Standards hereafter), while the other studies address the 2010 Voluntary Standards directly. Marri et al (2012a) analyzed economics standards for all 50 states for mention of the federal debt or deficit. They found that “our review yields one major conclusion: almost universally, state standards pay little or no attention to the federal budget, the budget deficit, or the federal debt” (p. 135).…”
Section: K-12 Economic Education Curriculum: Commentaries Studies Anmentioning
confidence: 99%
“…Social studies, a field that embraces and encourages the discussion of controversial issues, should be concerned about a curriculum that is admittedly free of “frictions” and “unresolvable conflict” which includes race, class, and gender (Weintraub, 2002) and that withholds the vital information people need in order to vote, make decisions, and engage in civil dialogue. Moreover, Marri and collaborators (Gans, 2015; Marri et.al., 2012a, 2012b) stressed the importance of students learning about the national debt and deficit because of the affect it has on their lives and wallets, and, yet, the sense-making tools students have at their disposal, neoclassic economic theory, could be insufficient to students’ abilities to fully understand the affective, political and social consequences of the national debt and deficit and its discursive deployment by politicians. In other words, in neoclassicism, humans have a very small, very specific, role to play (that of rational actor) with little room to imagine other possible subject positions and solutions to social problems.…”
Section: Two Critiques Of Neoclassicismmentioning
confidence: 99%
“…However, most youth in the USA do not have an adequate awareness of the concepts of the federal budget, national debt and budget deficit (Marri et al, 2012). Biennial findings of the Council for Economic Education on the state of economics education in the USA similarly agree that federal budget, national debt and budget deficit topics are not adequately treated at the secondary level (Marri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%